When is there a sustainability case for CSR? Pathways to environmental and social performance improvements - Minna Halme; Jukka Rintamaki; Jette Steen Knudsen; Leena Lankoski; Mika Kuisma (2018)
Little is known about when corporate social responsibility (CSR) leads to a sustainability case (i.e., to improvements in environmental and social performance). Building on various forms of decoupling, we develop a theoretical framework for examining pathways from institutional pressures through CSR management to sustainability performance. To empirically identify such pathways, we apply fuzzy-set qualitative comparative analysis (fsQCA) to an extensive dataset from 19 large companies. We discover that different pathways are associated with environmental and social performance (non)improvements, and that pathways to success and failure are for the most part not symmetrical. We identify two pathways to improved environmental performance: an exogenous and an endogenous one. We find two pathways to improved social performance that both involve integrating social responsibility into the core business. Pathways to nonimprovements are multiple, suggesting that failure can occur in a number of ways, while there are only a few pathways to sustainability performance improvements.